Epstein–Barr virus-positive pyothorax-associated lymphoma expresses CCL17 and CCL22 chemokines that attract CCR4-expressing regulatory T cells. (1st July 2019) - Higuchi, Tomonori; Matsuo, Kazuhiko; Hashida, Yumiko; Kitahata, Kosuke; Ujihara, Takako; Taniguchi, Ayuko; Yoshie, Osamu; Nakayama, Takashi; Daibata, Masanori
Abstract: Epstein–Barr virus (EBV)-positive diffuse large B-cell lymphomas associated with chronic inflammation (DLBCL-CI) develop in patients with chronic inflammation but without any predisposing immunodeficiency. Given the expression of the EBV latent genes, DLBCL-CI should have mechanisms for evasion of host antitumor immunity. EBV-positive pyothorax-associated lymphoma (PAL) is a prototype of DLBCL-CI and may provide a valuable model for the study of immune evasion by DLBCL-CI. This study demonstrates that PAL cell lines express and secrete CCL17 and/or CCL22 chemokines, the ligands of C–C motif chemokine receptor 4 (CCR4), in contrast to EBV-negative DLBCL cell lines. Accordingly, culture supernatants of PAL cell lines efficiently attracted CCR4-positive regulatory T (Treg) cells in human peripheral blood mononuclear cells. PAL cells injected into mice also attracted CCR4-expressing Treg cells. Furthermore, this study confirmed that CCR4-expressing Treg cells were abundantly present in primary PAL tissues. Collectively, these findings provide new insight into the mechanisms of immune evasion by PAL, and further studies are warranted on whether such mechanisms eventually lead to the development of DLBCL-CI. Highlights: PAL cell lines abundantly expressed CCL17 and/or CCL22 chemokines. The expression was upregulated by exogenous cytokines linked to inflammation. CCL17 and CCL22 secreted by PAL cell lines attracted Treg cells via CCR4. Primary PAL tissues can infiltrate CCR4-expressing Treg cells.